Penerapan Metode Grafik untuk Menghitung Keuntungan Maksimum Usaha Loambeaf pada Mata Kuliah Kewirausahaan Mahasiswa Pendidikan Matematika - Anisatul Islami; Aulia Kartika Syari; Dedek Kustiawati; Salwa Aisyah Salsabila (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The proposed research entitled "Application of the Graphical Method for Calculating Loambeaf's Maximum Business Profits in Mathematics Education Student Entrepreneurship Courses" aims to provide an analysis in terms of production planning so that the income is maximized. One of the mathematical sciences that can be used to solve this problem is a linear program with a graphical method. In the specialization course in the Mathematics Education Study Program, several students taking this course have a Food and Beverages (F&B) business. One such venture is Loambeef. The results of the analysis found that the existing Loambeef menu, namely beef cheese spring rolls and original beef spring rolls, group 5 entrepreneurial student businesses with one-time production will get a maximum income of Rp. 170,000 with a profit of Rp. 30,000 or 21% of the initial capital.